An iron-based core-shell catalyst for residual oil suspension bed hydrocracking and preparation method thereof

SiO2@ZnFe-LDHs iron-based core-shell catalyst was prepared by hydrothermal-coprecipitation method, which solved the problems of poor stability and high cost of existing catalysts in hydrocracking of residues, and achieved efficient residual oil conversion and gasoline and diesel collection. , suitable for industrial applications.

CN116273012BActive Publication Date: 2025-01-10FUZHOU UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310159620.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-01-10
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The existing residual oil hydrocracking catalysts have problems such as complex process, high cost, poor stability and rapid inactivation in heavy oil treatment. Especially due to the presence of impurities and coke, the catalyst activity is reduced, which is difficult to meet the needs of industrial applications.

Method used

The SiO2@ZnFe-LDHs binary hydrotalcite iron-based core-shell catalyst was prepared by hydrothermal-coprecipitation method, and a stable composite metal oxide was generated by calcination, providing metal active sites and oxygen defect sites, and improving the activity and stability of the catalyst. It is suitable for hydrocracking reaction of residual oil suspended bed.

Benefits of technology

It achieves high conversion rate and high gasoline and diesel yield, reduces the deactivation rate of the catalyst, improves the stability and dispersion of the catalyst, and is suitable for industrial-scale lightweight production of residual oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273012B_ABST
    Figure CN116273012B_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based core-shell catalyst for residual oil suspension bed hydrocracking and a preparation method thereof. First, a hydrothermal-coprecipitation method is used to prepare in situ a SiO2@ZnFe-LDHs binary hydrotalcite iron-based catalytic material with a core-shell structure. After roasting in an air atmosphere, an iron-based core-shell catalyst (SiO2@ZnFe-LMOs) is obtained. The prepared catalyst has low particle size and can be highly dispersed in a residual oil medium. At the same time, the specific surface area of ​​the catalytic material is relatively large, which helps the residual oil to fully contact the catalyst. This type of catalyst is applied to residual oil suspension bed hydrocracking, has a higher hydrogenation activity, effectively suppresses the generation of gaseous small molecules and coke, improves the residual oil molecule utilization rate, and the product gasoline and diesel yield is higher than 50%, and has a higher conversion rate and liquid yield, which will have a good application prospect in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy chemical industry, and specifically relates to an iron-based core-shell catalyst material and a preparation method thereof, and application thereof in the production of light oil by residual oil suspension bed hydrocracking. Background Art

[0002] Since the 21st century, the world's conventional crude oil resources have become increasingly scarce, and crude oil resources have shown a very significant trend of becoming heavier and inferior. Today, the world's remaining oil resources are about 10 trillion barrels, of which heavy oil resources account for 70% and conventional oil resources only 30%. In recent years, the world's heavy oil production costs have continued to decline with the improvement of development technology and management level, and the growth rate of global conventional crude oil development and production has been far lower than that of heavy oil development and production. In the future, the industrial production scale of heavy oil will occupy an increasingly large proportion in the refining industry.

[0003] Residue oil hydrogenation technology is highly favored for its high conversion rate, high light oil yield, good product quality, good device efficiency and excellent environmental performance. Therefore, the residue oil hydrogenation process will continue to be the main treatment method for inferior heavy oil processing technology in the future, and it is also the most reasonable and effective way to solve the deep processing of heavy oil. At present, the catalysts for industrial residue oil suspension bed hydrocracking are mainly divided into homogeneous catalysts (water-soluble catalysts and oil-soluble catalysts) and solid powder catalysts.

[0004] CN 110237851 A, CN 110237866 A and CN 107469837 B disclose one or more homogeneous dispersed catalysts for inferior heavy oil and residual oil. Such catalysts can obtain a higher hydrogenation conversion rate, have higher selectivity and stability, and can effectively inhibit coking during the reaction process. However, the preparation of these catalysts has the problems of complex process and high cost, and the catalyst recovery is difficult.

[0005] CN 103769196 B discloses a residual oil hydrocracking catalyst that can be prepared by a coprecipitation method, wherein the catalyst contains 2-20 wt% of hydrated iron oxide, 27-55 wt% of molecular sieve, and 30-70 wt% of a heat-resistant inorganic oxide carrier, and is suitable for use in the hydrocracking process of super-heavy oil and inferior residual oil with high asphaltene and metal content, and has the advantages of simple preparation method, no precious metal, low cost, and high light oil yield. CN101491764 B discloses a residual oil hydrocracking catalyst prepared by loading active components (active components include VIB and VIII group active metal components, the VIII group metal is Ni or Co, and the VIB group metal is W or Mo) by modifying kaolin, and the prepared catalyst can be used in the fields of hydrodemetallization, hydrodesulfurization, and hydroconversion of heavy oil or residual oil, and has good performance.

[0006] As a functional material with a layered structure, hydrotalcite (LDH) has excellent catalytic performance and has great advantages in residual oil hydrocracking. Silicon dioxide (SiO2) is an inorganic substance. As one of the commonly used carriers, it has a large specific surface area and rich void structure, and its chemical properties are relatively stable, which is conducive to the loading and dispersion of active metals. CN 107115853 A discloses a MgAl-type hydrotalcite catalyst for treating heavy oil. The MgAl-type hydrotalcite catalyst can be directly used for conventional catalytic cracking to produce high-quality gasoline and diesel; the catalyst has strong hydrothermal resistance, and the gasification regeneration technology used uses a mixture of water vapor and air as the regeneration gas to obtain a synthesis gas with an H / C ratio of about 1, which can be used for a one-step diesel production process or the production of chemical products such as olefins and aromatics, realizing the maximum utilization of resource value. However, its liquid yield is low, and the large amount of solid coke generated accelerates the deactivation of the catalyst.

[0007] At present, the production of light oil by residue hydrocracking technology is mainly based on fixed bed reaction process. However, the residue raw materials used in the residue hydrocracking process inevitably contain a large amount of impurities and toxic substances, which accelerate the deactivation of the catalyst, which will be a great challenge to the stability of the catalyst. At the same time, coke will be produced during the reaction process. Impurities, poisons and coke enriched on the surface of the catalyst seriously reduce the activity of the catalyst, resulting in rapid deactivation of the catalyst. Therefore, it is of vital importance to develop a new process for residue hydrocracking. The characteristic of the suspended bed reaction process is that the catalyst and raw materials pass through the reactor at one time, which can well avoid the problem of catalyst deactivation due to the presence of impurities and coke. Based on the characteristics of the suspended bed hydrogenation reaction, this requires the catalyst to have the characteristics of high activity, low price and good stability.

[0008] In summary, it is very necessary to develop a suspended bed hydrocracking catalyst with high activity, good hydrogenation performance, low cost and good stability in the processing of residual oil. The key lies in how to select materials with high hydrocracking activity and low price as active components, and at the same time prepare highly dispersed and stable catalysts. To achieve this effect, we invented an iron-based core-shell catalytic material to lighten the residual oil. The preparation process of this material is green and simple, and the raw materials are cheap. There are few reports on the application of this iron-based core-shell catalyst material in the field of residual oil suspended bed hydrocracking production, which has very important guiding significance and practical value for the production of residual oil lightening. Summary of the invention

[0009] The purpose of the present invention is to apply iron-based core-shell catalytic materials to the production of residual oil suspension bed hydrocracking. Using SiO2@ZnFe-LDHs binary hydrotalcite iron-based catalytic materials with core-shell structure as precursors, after calcination, iron-based core-shell catalytic materials (SiO2@ZnFe-LMOs) with tightly packed crystal units and stable composite metal oxides can be generated. The metal active sites and oxygen vacancies are conducive to the hydrocracking reaction, and the stability is good. The specific surface area of ​​the synthesized catalyst is relatively large, which is conducive to the combination of macromolecules in the raw materials. The catalyst shows excellent catalytic performance in the residual oil suspension bed hydrocracking reaction, with a high residual oil conversion rate and a high gasoline and diesel yield. The prepared iron-based core-shell catalyst material has good application prospects in the residual oil suspension bed hydrocracking reaction.

[0010] To achieve the above object, the present invention adopts the following technical solution:

[0011] A method for preparing an iron-based core-shell catalyst for residual oil suspension bed hydrocracking is to use a hydrothermal-coprecipitation method to react carbonate and hydroxide generated by a mixed alkali with zinc and iron metal salt ions under certain temperature conditions to generate a binary hydrotalcite (ZnFe-LDHs) intercalated with carbonate combined with SiO2, and after calcination in an air atmosphere, an iron-based core-shell catalyst material (SiO2@ZnFe-LMOs) with highly dispersed active components and good stability is obtained. Specifically, the following steps are included:

[0012] (1) mixing a metal iron salt and a zinc salt in a certain molar ratio, dissolving them in deionized water, and stirring until they are completely dissolved to form a mixed metal salt solution;

[0013] (2) mixing alkaline substances in a certain molar ratio, dissolving them in deionized water, and stirring until they are completely dissolved to form an alkaline solution;

[0014] (3) slowly adding the alkaline solution dropwise to the vigorously stirred mixed metal salt solution, and adding SiO2 to form a uniform suspension, and then vigorously stirring and aging at room temperature for 0.5-12 h;

[0015] (4) transferring the aged suspension in step (3) to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner, statically crystallizing at 70-180°C for 6-48 hours, taking out and cooling to room temperature, filtering the precipitate, washing it, and drying it in an oven at 80-180°C for several hours to obtain a binary hydrotalcite-like iron-zinc core-shell catalyst precursor;

[0016] (5) The binary hydrotalcite iron-zinc core-shell catalyst precursor obtained in step (4) is calcined at 300-800° C. in an air atmosphere for 2-12 h, and then cooled to obtain an iron-based core-shell catalyst.

[0017] Furthermore, the metal iron salt in step (1) is any one of ferric nitrate, ferric acetate, ferric chloride, ferric oxalate or ferric sulfate; and the zinc precursor is any one of zinc nitrate, zinc sulfate, zinc chloride or zinc acetate.

[0018] Furthermore, in step (1), the molar ratio of zinc ions to iron ions is 1:0.1-10.

[0019] Furthermore, the alkaline substance described in step (2) is at least one of NaOH, KOH, LiOH, ammonia water, Na2CO3, K2CO3, Li2CO3, (NH4)2CO3, NH4HCO3, urea, water, hydrazine and hexamethylenetetramine.

[0020] Furthermore, in steps (1) and (2), the molar concentration of the mixed metal salt solution is 0.1-10 mol / L, and the molar concentration of the alkaline solution is 0.1-20 mol / L.

[0021] Furthermore, in step (3), the rate of vigorous stirring is 300-1500 r / min, and the aging time is 0.5-12 h.

[0022] Furthermore, in step (4), the crystallization temperature is 70-180°C, and the crystallization time is 6-48 h;

[0023] Furthermore, in step (5), the calcination atmosphere is air, the calcination temperature is 300-800°C, and the calcination time is 2-12h.

[0024] The above-mentioned iron-based core-shell catalyst for residual oil suspension bed hydrocracking is used in the production of light oil by residual oil hydrocracking. The specific application method is: vacuum residual oil and the iron-based core-shell catalyst are placed in a Hastelloy reactor simulating a suspended bed reactor, the air in the reactor and the pipeline is purged with nitrogen, and then high-purity hydrogen is filled in the suspended bed reactor for hydrocracking reaction. The reaction conditions are: temperature 350-430 ℃ (preferably 400-430 ℃), hydrogen pressure 5-11MPa (preferably 7-9 MPa), stirring rate 300-1000 rpm / min (preferably 300-800 rpm / min), catalyst dosage 0.5-5%, and the hydrocracking reaction product is filtered and distilled to obtain naphtha, gasoline and diesel, and wax oil. The residual oil is one of the industrial residual oils.

[0025] The invention is innovative in that:

[0026] (1) The preparation process of the iron-based core-shell catalyst material provided by the present invention is green and simple, the catalyst raw material cost and preparation cost are low, the prepared catalyst has metal active sites and oxygen defect sites, which are conducive to the hydrocracking reaction, good stability, active components are not easy to lose, and the specific surface area is large, which is conducive to the binding of macromolecules in the raw materials.

[0027] (2) The catalyst prepared by the present invention is used for the first time in the residual oil suspension bed hydrocracking process, with a high residual oil conversion rate and a high gasoline and diesel yield, and has good application prospects in industry.

[0028] (3) The addition of SiO2 can significantly improve the dispersion of active metals on the SiO2 surface and reduce the agglomeration of active metals. The reduction of metal agglomeration reduces the size of catalyst particles. At the same time, the addition of non-metallic SiO2 significantly reduces the density of catalyst powder and improves the dispersion and stability of the catalyst in residual oil. When SiO2 is not added, the performance of bimetallic oxides in inhibiting the formation of gas coke will be greatly reduced. When used in the residual oil suspension bed hydrocracking reaction, although the gasoline and diesel yields are comparable to those of SiO2@ZnFe-LMOs iron-based core-shell catalysts, the gas coke yield is significantly increased. The large amount of coke produced will quickly deactivate the catalyst, which is not conducive to the industrial use of residual oil suspension bed hydrocracking.

[0029] (4) The preparation method of this catalyst is also applicable to other metals. Generally speaking, divalent metal ions M that can enter the hydrotalcite layer are 2+ With trivalent metal ions M 3+ should have similar ionic radii. 3+ Fe 3+ When M 2+ It can also be Cu 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ Mg 2+ etc. SiO2 can be of different particle sizes and specifications. In the application of residual oil suspension bed hydrocracking, ZnFe bimetallic exhibits better hydrogenation activity and gas coke inhibition performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the SiO2 powder material in Example 1.

[0031] Figure 2 This is the SEM image of the iron-based core-shell catalyst material prepared in Example 1.

[0032] Table 1 shows the conversion rate and gasoline and diesel yield of the iron-based core-shell catalysts prepared in Examples 1-6 for suspended bed hydrocracking reactions.

[0033] Table 2 is a comparison of the gasoline and diesel yields and gas coke yields of the iron-based core-shell catalyst prepared in Example 1 and the pure hydrotalcite-like material prepared without adding SiO2 in the suspended bed hydrocracking reaction. DETAILED DESCRIPTION

[0034] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0035] The raw materials are all reagent grade. The prepared catalyst is used for residual oil suspension bed hydrogenation reaction. After the reaction is completed, the reaction product is experimentally evaluated by vacuum distillation: the distillation sections <180 ℃, 180~350 ℃, 350~500 ℃ and >500 ℃ are quantitatively analyzed, and the residual oil conversion rate, liquid yield, gasoline and diesel yield, and gas coke yield of the reaction are calculated.

[0036] Example 1

[0037] 0.006 mol Zn(NO3)2•6H2O and 0.014 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.007 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, then vigorously stirred and aged at room temperature for 1 h, the aged suspension was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner, statically crystallized at 120 °C for 12 h, taken out and cooled to room temperature, the precipitate was filtered, washed and dried in an oven at 120 °C for several hours to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 h to obtain an iron-based core-shell catalyst material.

[0038] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0039] Example 2

[0040] 0.002 mol Zn(NO3)2•6H2O and 0.018 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.009 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, and then vigorously stirred and aged at room temperature for 1 h. The aged suspension was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and then placed in an oven for static crystallization at 120 °C for 12 h, then taken out and cooled to room temperature, filtered, washed and precipitated, and placed in an oven at 120 °C to constant weight to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 hThe iron-based core-shell catalyst material is obtained.

[0041] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0042] Example 3

[0043] 0.01 mol Zn(NO3)2•6H2O and 0.01 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.005 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, then vigorously stirred and aged at room temperature for 1 h, the aged suspension was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, statically crystallized at 120 °C for 12 h, taken out and cooled to room temperature, the precipitate was filtered, washed and dried in a 120 °C oven for several hours to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 h to obtain an iron-based core-shell catalyst material.

[0044] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0045] Example 4

[0046] 0.006 mol Zn(NO3)2•6H2O and 0.014 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.007 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, then vigorously stirred and aged at room temperature for 1 h, the aged suspension was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner, statically crystallized at 140 °C for 12 h, taken out and cooled to room temperature, the precipitate was filtered, washed and dried in an oven at 120 °C for several hours to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 h to obtain an iron-based core-shell catalyst material.

[0047] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0048] Example 5

[0049] 0.006 mol Zn(NO3)2•6H2O and 0.014 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.007 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, then vigorously stirred and aged at room temperature for 1 h, the aged suspension was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner, statically crystallized at 160 °C for 12 h, taken out and cooled to room temperature, the precipitate was filtered, washed and dried in an oven at 120 °C for several hours to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 h to obtain an iron-based core-shell catalyst material.

[0050] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0051] Example 6

[0052] 0.006 mol Zn(NO3)2•6H2O and 0.014 mol Fe(NO3)3•9H2O were dissolved in 100 ml deionized water to form solution A, 0.04 mol NaOH and 0.007 mol Na2CO3 were added to 80 ml deionized water to obtain a clear solution B, solution B was slowly added dropwise to the vigorously stirred solution A to form a uniform suspension, and silica powder was added, then vigorously stirred and aged at room temperature for 1 h, the aged suspension was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner, statically crystallized at 120 °C for 24 h, taken out and cooled to room temperature, the precipitate was filtered, washed and dried in an oven at 120 °C for several hours to obtain a binary hydrotalcite iron-zinc core-shell catalyst precursor, and then the obtained binary hydrotalcite iron-zinc core-shell catalyst precursor was placed in a muffle furnace and calcined at 500 °C for 6 h to obtain an iron-based core-shell catalyst material.

[0053] 40 g of residual oil and 1.2 g of iron-based core-shell catalyst material were loaded into a Hastelloy reactor simulating a suspended bed reactor. The air in the reactor and the pipeline was purged with nitrogen. Then, 6 MPa of high-purity hydrogen was filled in the suspended bed reactor for hydrogenation reaction. The reaction conditions were: temperature 430 °C, hydrogen pressure 6 MPa, stirring rate 600 rpm / min. The products after hydrocracking were separated by filtration, and the liquid products were analyzed.

[0054] Figure 1 This is the SEM image of SiO2 spherical powder with a particle size of 400-500 nm. It can be seen that its surface is very smooth.

[0055] Figure 2 The SEM image of the iron-based core-shell catalyst synthesized by the method of this patent uses SiO2 balls with a particle size of 400-500 nm as the core. It can be seen that the fine lamellar metal oxides grown on the surface of the SiO2 balls wrap them, which is similar to a core-shell structure.

[0056] Table 1 shows the conversion rate and gasoline and diesel yield of the iron-based core-shell catalysts prepared in Examples 1-6 for residual oil suspension bed hydrocracking.

[0057]

[0058]

[0059] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An application of an iron-based core-shell catalyst in the production of light oil by residual oil suspension bed hydrocracking, characterized in that: The preparation of the iron-based core-shell catalyst comprises the following steps: (1) Mix the metal iron salt and the zinc salt, dissolve them in deionized water, and stir until they are completely dissolved to form a mixed metal salt solution; (2) mixing the alkaline substances, dissolving them in deionized water, and stirring until they are completely dissolved to form an alkaline solution; (3) slowly adding the alkaline solution dropwise to the vigorously stirred mixed metal salt solution, and adding silica powder to form a uniform suspension, then vigorously stirring at room temperature and aging for 0.5-12 h; (4) transferring the aged suspension in step (3) to a hydrothermal reactor, statically crystallizing for 6-48 h, taking out and cooling to room temperature, filtering and washing the precipitate, and drying it in an oven at 80-180° C. to obtain a binary hydrotalcite-like iron-zinc core-shell catalyst precursor; (5) calcining the binary hydrotalcite-like iron-zinc core-shell catalyst precursor obtained in step (4) at 300-800° C. in an air atmosphere for 2-12 h, and cooling the resulting iron-based core-shell catalyst for residual oil suspension bed hydrocracking; The specific application method is to put vacuum residue oil and the iron-based core-shell catalyst into a suspended bed reactor, fill the suspended bed reactor with high-purity hydrogen for a hydrocracking reaction, and the reaction conditions are: temperature 350-430 ° C, hydrogen pressure 5-11 MPa, stirring rate 300-1000 rpm / min, and the amount of the iron-based core-shell catalyst is 0.5-5wt% of the vacuum residue oil.

2. The use according to claim 1, characterized in that: The metal iron salt in step (1) is any one of ferric nitrate, ferric acetate, ferric chloride, ferric oxalate and ferric sulfate; the zinc salt is any one of zinc nitrate, zinc sulfate, zinc chloride and zinc acetate.

3. The use according to claim 1, characterized in that: In step (1), the molar ratio of zinc ions to iron ions is 1:0.1-10, and the molar concentration of the mixed metal salt solution is 0.1-10 mol / L.

4. The use according to claim 1, characterized in that: The alkaline substance described in step (2) is at least one of NaOH, KOH, LiOH, ammonia water, Na2CO3, K2CO3, Li2CO3, (NH4)2CO3, NH4HCO3, urea, and hexamethylenetetramine.

5. The use according to claim 1, characterized in that: The molar concentration of the alkaline solution in step (2) is 0.1-20 mol / L.

6. The use according to claim 1, characterized in that: In step (3), the stirring rate is 300-1500 rpm / min, and the aging time is 0.5-12 h.

7. The use according to claim 1, characterized in that: In step (4), the crystallization temperature is 80-300°C and the crystallization time is 6-48h.

8. The use according to claim 1, characterized in that: The calcination temperature in step (5) is 300-800°C and the calcination time is 2-12 h.

Citation Information

Patent Citations

  • Residual oil hydrogenation catalyst and preparation method and use thereof

    CN101491764B

  • A residue oil hydrogenation catalyst, its preparation method and its application

    CN103769196B

  • Mg-Al hydrotalcite-like compound catalyst for treating residual oil and extra heavy oil material and preparation method of Mg-Al hydrotalcite-like compound catalyst

    CN107115853A

  • Self-sulfurized oil-soluble NiMo catalysts, their preparation methods and applications

    CN107469837B

  • Oil-soluble catalyst and preparation method and application thereof

    CN110237851A